The effect of listed firms' profitability on the market value of their common stock: Evidence from Malaysia - Mohammadabadi, Siamak Beizaie (2008)
This research tries to investigate the relationship between the ratio of Market-to-Book value (M/B) as a determinant of a stock's value creation and return on Equity (ROE) as a measure of corporate profitability.